Determining a Midday Stem Water Potential Threshold for Irrigation of Table Grapes: Water potential threshold - Myburgh, P.; Howell, C. L. (South African Journal of Enology and Viticulture, 2022)
Sustainable table grape production depends on efficient water supply. Water potential is a useful indicator of water constraints in grapevines. In this regard, midday stem water potential (ΨS) is considered to be a better indicator of grapevine water status than leaf water potential (ΨL). The objective of the study was to determine a water potential threshold to set soil water refill lines for table grape irrigation. However, in previous studies carried out locally, only ΨL was measured. The relationship between ΨS and ΨL was determined for ten selected table grape cultivars. Since there were no differences between cultivars, a single equation could be used to convert midday ΨL measured in previous studies with table grapes to ΨS. Vegetative growth, berry mass and colour, as well as juice total soluble solids (TSS) data were pooled, and related to midday ΨS. This showed that -0.8 MPa seems to be a ΨS threshold for water constraints in the pre-harvest period that will allow sustainable growth and berry size for anisohydric table grape cultivars. The optimum ΨS for berry colour is between -0.8 MPa and -1.0 MPa. Consequently, a midday ΨS threshold of -0.8 MPa can be used to set refill points for irrigation where soil water content is measured on a regular basis in table grape vineyards.